Reproductive performance primarily depends on the female genotype in a two-factorial breeding experiment using high-fertility mouse lines. Issue 3 (March 2017) - Langhammer, Martina; Michaelis, Marten; Hartmann, Michaela F; Wudy, Stefan A; Sobczak, Alexander; Nürnberg, Gerd; Reinsch, Norbert; Schön, Jennifer; Weitzel, Joachim M
Abstract : Mouse models showing an improved fertility phenotype are barely described in the literature. In the present study, we further characterized two outbred mouse models that have been selected for the phenotype 'high fertility' for more than 177 generations (fertility lines (FL) 1 and 2). In order to delineate the impact of males and females on fertility parameters, we performed a two-factorial breeding experiment by mating males and females of the three different genotypes (FL1, FL2, unselected control (Ctrl)) in all 9 possible combinations. Reproductive performance, such as number of offspring per litter or total birth weight of the entire pup, mainly depends on the female genotype. Although the reproductive performance of FL1 and FL2 is very similar, their phenotypes differ. FL2 animals of both genders are larger compared to FL1 and control animals. Females of the control line delivered offspring earlier compared to FL1 and FL2 dams. Males of FL1 are the lightest and the only ones who gained weight during the two weeks mating period. To address whether this effect is correlated with differing serum androgen levels, we measured the concentrations of testosterone, dehydroepiandrosterone, 4-androstenedione, androstanediol and dihydrotestosterone in males of all three lines by GC–MS. We measured serum testosterone between 5.0 and 6.4 ng/mL, whereas the concentrations of the other androgens were at least one order of magnitude lower, with no significant differences between the lines. Our data indicate that reproductive outcome largely depends on the genotype of the female in a two-factorial breeding experiment and supports previous findings that the phenotype 'high fertility' is warranted by using different physiological strategies.